Illegal competitive advantages, the development of the industry of illegal drugs and the failure of policies against drugs in afghanistan and colombia (2005)
In 1970 Colombia was not known for its cocaine or illegal drugs production and Afghanistan was and had been for a long time a minor producer of opium. In fact, opium had not been a “traditional” crop in Afghanistan and before the nineties it had been grown only in a few places around the country.Unlike the majority of the countries in this region, Afghanistan showed a weak “opium culture”. In this time neither of these two countries was an important producer of cocaine or opium, or an important actor in the illicit drugs international markets. This article, examines how they are actually the dominant countries in the illegal industry of the two most important branches of vegetal origin: coca, cocaine and poppy-opium-heroine.